The Concept of Children’s Emotional Development in Full Day School Education System - Khayati, Ni’matul (Proceeding International Conference on Religion, Science and Education, 2025)
Full-day school education is gaining popularity in Indonesia as a solution for busy parents and a strategy to enhance educational quality. However, concerns persist about its potential impact on children's emotional development. This article aims to review the literature on children's emotional development within the context of full-day school systems. Employing a literature review approach, the article explores how extended school hours, prolonged social interactions, and teaching methods may influence children's emotional growth. The researchers initially reviewed 14 sources, which were then refined to 10. Findings from the literature indicate that, while there are potential benefits—such as increased independence and emotional regulation—there are also challenges, including emotional fatigue and stress, which must be considered in policy development for full-day school education.